Analisa Peranan Aliansi Petani Padi Organik Boyolali dalam Peningkatan Status Sosial Ekonomi Petani Padi Organik di Boyolali. - suswadi; Arganata Yuda Prastya Yuana; Agung Prasetyo; Mahananto (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
The aims of this study were: 1) To find out the role of APPOLI in organic rice farming to improve the socio-economic status of organic rice farmers. 2) To find out the income of organic rice farming in improving the socio-economic status of rice farmers. 3) To find out the relationship between the role of APPOLI and the income of organic rice farming in improving the socio-economic status of organic rice farmers. The results of the five (5) indicators have a significant role evident from the activeness and participation of each member of the farmer group in carrying out the activities in the farmer group is classified as high on average per the fifth indicator (5) the indicator has an average scoring percentage of 85%, which means the fifth (5) the indicator has a relatively high scoring value. For organic rice farming income, the average revenue is IDR 12,474,633 and the average production cost is IDR 4,012,350. So it can be concluded that the average income of organic rice farmers per planting season (MT) is IDR 8,462,283. The role of APPOLI partially has a relationship with income in terms of the strength of the relationship between variables included in the strong category, which is around 0.687 (Adjusted Rsquere) and so the criteria received in this research is criterion 1, namely test f <with sig ? (error rate ) then it has a real relationship or if the T-test per indicator < sig ? (error rate) then it has a real relationship and the 2nd criterion is rejected for per indicator basis it can be concluded that the (4) indicators are places of cooperation, organic certification, seed assistance, and the learning class has a significant relationship with the income of paddy rice farming and for this farmer insurance indicator, it has no relationship with income because the sig value on farmer insurance is > than sig ? 5% (error rate).